Políticas de desenvolvimento regional-territorial e governança: uma análise recente sobre o Estado do Maranhão (Brasil) - Carvalho, Fernanda Cunha de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The related research is concerned with the theme of development, given its importance in the face of geographical analysis (with focus on Economic and Regional Geography) confirming the maintenance of a necessary dialogue with other areas of science. Observation of Maranhão (situated in the context of Brazil and the Northeast) was sent by the thesis that portrays that failure of regional- territorial development in the state, beyond the structuralist elements, must be simultaneously analyzed together with the governance practices, which It has not achieved its operational dimension and disregards the basic principles of a widespread and democratic proposal on an applied development at the local level. Therefore, there was the help of bibliographic references, documentary and cartographic and conducting quantitative research (powered by databases) and qualitative (strengthened by interviews in government institutions). Upon this overview, Maranhão, can be set as a politically and economically, dependent state, the concentration of power and wealth in state figures, large companies and some territories reflected in the indexes data that demonstrate the high degree of inequalities sites. Still, it found certain evolution and expansion in discussions on the development and introduction of the possibility of social participation in political decisions, it is considered a comparison of the government plans and multi-annual plans. However, there has been a more discursive evolution rather than operational, demonstrating the fragility of the governance. The performed approach indicates that it considers to be far from reaching a conclusion about the possibilities surrounding the development in Maranhão, however, to emphasizes the needs, to create strategies that optimize economic growth, but that go beyond this line, which indicates that it should set goals for the territories previously invisible, being the main government interests focuses...

Esta pesquisa preocupa-se com a temática do desenvolvimento, dada sua importância diante da análise geográfica (com foco na Geografia Econômica e Regional), confirmando a manutenção de um necessário diálogo com outras áreas da ciência. A observação do Maranhão (situado no contexto do Brasil e do Nordeste) foi encaminhada pela tese que retrata que o insucesso do desenvolvimento territorial no estado deve ser contemporaneamente analisado não apenas nos seus aspectos estruturais, mas também junto à fragilidade das práticas de governança, que não têm alcançado a sua dimensão operacional e desconsidera os princípios básicos de uma proposta difusa e democrática sobre um desenvolvimento aplicado em âmbito local. Para tanto, houve o auxílio de referenciais bibliográficos, documentais e cartográficos e a realização de pesquisas quantitativas (alimentadas por bases de dados) e qualitativas (fortalecidas por entrevistas em instituições governamentais). De forma geral, o Maranhão pode ser caracterizado como ainda bastante dependente, política e economicamente, da concentração de poder e riqueza nas figuras do Estado, das grandes empresas e de alguns territórios, dados refletidos nos índices que demonstram o elevado grau das desigualdades locais. Ainda assim, é constatada certa evolução e ampliação nas discussões sobre o desenvolvimento e na introdução da possibilidade de participação social nas decisões políticas, se for considerada uma comparação entre os planos de governo e os planos plurianuais. No entanto tem havido uma evolução mais discursiva do que operacional, demonstrando a fragilidade da governança. A abordagem efetuada indica que se considera estar longe de se chegar a uma conclusão sobre as possibilidades em torno do desenvolvimento maranhense, contudo ressalta-se a necessidade de se criarem estratégias que otimizem o crescimento econômico, extrapolando essa vertente. Indica-se que se...
Keywords: Economic geography; Geografia econômica; Políticas públicas; Planejamento regional; Governança; Geografia regional; Maranhão (MA)